Benzylidene‐indolinones are effective as multi‐targeted kinase inhibitor therapeutics against hepatocellular carcinoma. Issue 7 (2nd May 2014) - Ho, Han Kiat; Chua, Boon Tin; Wong, Winnie; Lim, Kah Suan; Teo, Vivian; Ong, Hooi-Tin; Chen, Xiao; Zhang, Wei; Hui, Kam M.; Go, Mei Lin; Ullrich, Axel
Abstract : Effective pharmacological intervention of advanced hepatocellular carcinoma (HCC) is currently lacking. Despite the use of tyrosine kinase inhibitors (TKIs) for the targeted therapy of several malignancies, no agent has been developed to specifically interfere with the oncogenic tyrosine kinase signaling aberrations found in HCC. Therefore, we adopted an orthogonal biological phenotypic screening approach to uncover candidate compounds: based on a potent cytotoxicity toward HCC‐derived cell lines, and minimal toxicity toward normal liver cells. Given the success of indolinone as a chemical scaffold in deriving potent multi‐kinase inhibitors (e.g. sunitinib), we screened a group of newly synthesized benzylidene‐indolinones. Among the candidates, E/Z 6‐Chloro‐3‐(3‐trifluoromethyl‐benzyliden)‐1, 3‐dihydroindol‐2‐one (compound 47) exhibited potent anti‐proliferative, anti‐migratory, pro‐apoptotic properties and good safety profile as compared to known multi‐targeted tyrosine kinase inhibitors sunitinib and sorafenib. Additionally, an accompanying suppression of alpha‐fetoprotein (AFP) transcription, an HCC tumor marker, implies a favorable selectivity and efficacy on HCC. The in vivo efficacy was demonstrated in an HCC xenograft where 47 was administered once weekly (60 mg/kg) and suppressed tumor burden to the same extent as sorafenib (30 mg/kg daily). A receptor tyrosine kinase (RTK) array study revealed promising inhibition of multiple tyrosine kinases such as IGF‐1R, Tyro3 and EphA2 phosphorylation. Gene silencing of these targets ameliorated the cytotoxic potential of 47 on the HuH7 cell line, thereby implicating their contribution to the tumorigenicity of HCC. Hence, 47 exhibits potent anti‐cancer effects on HCC cell lines, and is a suitable lead for developing multi‐targeted kinase inhibitors of relevance to HCC. Highlights: A phenotype‐based screening of novel indolinones uncovers potent agents against HCC. Design helps identify effective compounds with minimal effect on healthy hepatocytes. 47 Exhibits superior anti‐cancer properties vs. sunitinib, including AFP suppression. In vivo efficacy of 47 was demonstrated with orthotopic HCC model. Inhibition of multiple tyrosine kinases contribute to the observed effects.